2016
DOI: 10.1108/prog-10-2015-0069
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the uses of mobile technology among Library and Information Science undergraduate students

Abstract: Purpose Mobile technology has redefined the way people communicate and interact. In education, the number of academic institutions developing and offering mobile information services is growing steadily. The purpose of this paper is to identify the use of mobile technology by the Library Science and Information Systems undergraduate students in Greece. Design/methodology/approach A questionnaire was developed drawing from the relevant literature and sent to undergraduate students studying Library and Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…However, usage of smartphones for reading journal articles, e-books, as well as searching the library catalogue was minimal. These findings reflected those obtained in a study by Vassilakaki, Moniarou-Papaconstantinou and Garoufallou (2016) in Greece in that they show that, as much as respondents were prepared to use their smartphones for academic and library-related activities, such usage was much lower when compared to that of other technological devices such as laptops. Respondents in the study by Lo et al (2016) indicated that the difficulty of browsing information on smartphones due to the design of the websites and applications made it problematic for them to utilise their smartphones for this purpose.…”
Section: Uses Of Mobile Phones Among Studentssupporting
confidence: 64%
See 4 more Smart Citations
“…However, usage of smartphones for reading journal articles, e-books, as well as searching the library catalogue was minimal. These findings reflected those obtained in a study by Vassilakaki, Moniarou-Papaconstantinou and Garoufallou (2016) in Greece in that they show that, as much as respondents were prepared to use their smartphones for academic and library-related activities, such usage was much lower when compared to that of other technological devices such as laptops. Respondents in the study by Lo et al (2016) indicated that the difficulty of browsing information on smartphones due to the design of the websites and applications made it problematic for them to utilise their smartphones for this purpose.…”
Section: Uses Of Mobile Phones Among Studentssupporting
confidence: 64%
“…Other studies have pointed to technological characteristics associated with mobile phones such as the small screen size, slow internet speed and cost of accessing services as factors militating against access to library services offered through mobile phones (Luo 2014, De Wee 2013. Nevertheless, the small screen size of most mobile phones, slow internet speed and cost, among others, seem not to have affected university students' use of mobile phone for social or communication purposes (Lo et al 2016, Vassilakaki, Moniarou-Papaconstantinou & Garoufallou 2016. Thus, other challenges beyond what is stated in the literature exist that affect usage of mobile phones for accessing library services.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations